Implementasi Program Tahfidz di SDI Ash Shiddiq Buduran Sidoarjo Tahun Pelajaran 2022/2023 - Syafi, Moh. Agus Syairofi; Nihayah, Khummaidatun (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
This article discusses the role of education, especially Islamic religious education, in developing students' spiritual intelligence. The main focus is on the Tahfidzul Qur'an program, which is of concern to the wider community. Islamic education is directed at forming individuals with high moral standards, or akhlaqul karimah, according to the teachings of the Islamic religion. Memorizing the Koran is considered a noble endeavor, as an effort to maintain the authenticity and purity of Islamic teachings. However, there are challenges in the tahfidz process, including lack of student motivation, internal and external obstacles, and lack of parental support. This research was conducted at SDI Ash Shiddiq Buduran Sidoarjo using qualitative research methods. The research results show that the implementation of the tahfidz program experienced successes and challenges. Parental support, effective management and teacher creativity in inspiring students are determining factors for success. However, several obstacles, such as lack of student enthusiasm and lack of ability to read the Qur'an, were also identified. Efforts to overcome barriers include providing supervising instructors, increasing collaboration with parents, and applying creative methods in learning.